Contemporary Chicana poetry : a critical approach to an emerging literature - Sánchez, Marta Ester (Berkeley : University of California Press, 1985)
Discusses 4 Chicana poets' "dilemmas of their dual relationship to American and Mexican societies and of their dual identity as Chicanas and as women writing in a contemporary setting."
Setting the context: gender, ethnicity, and silence in contemporary Chicana poetry -- The birthing of the poetic "I" in Alma Villanueva's Mother, may I/? the search for a female identity -- The Chicana as scribe: Harmonizing gender and culture in Lorna Dee Cervantes' "Beneath the shadow of the Freeway" -- Prohibition and sexuality in Lucha Corpi's Palabras de mediodía/Noon words -- The dramatization of a shifting poetic consciousness: Bernice Zamora's Restless serpents -- Appendixes: Poems from Bloodroot by Alma Villanueva ; Poems from Alma Villanueva's Irvine Collection ; Mother, may I? by Alma Villanueva.
Includes bibliographical references (pages 361-366) and index.
Print version record.
English, with some poetry in Spanish.
JSTOR
Keywords: American poetry -- Mexican American authors -- History and criticism; American poetry -- Women authors -- History and criticism; American poetry -- 20th century -- History and criticism; Mexican American women in literature; Spanish poetry -- Mexican American authors -- History and criticism; Spanish poetry -- Women authors -- History and criticism; Spanish poetry -- 20th century -- History and criticism; Poésie américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique; Poésie américaine -- 20e siècle -- Histoire et critique; Poétesses américaines d'origine mexicaine; Américaines d'origine mexicaine dans la littérature.; POETRY -- American -- General; American poetry; American poetry -- Mexican American authors; American poetry -- Women authors; Mexican American women in literature; Chicanos; Frauenlyrik; Lyrik; Gedichten; Vrouwen; Spaans; Amerikaans; Mexicanen; Chicanos; 1900-1999; Geschichte 1970-1985.; Criticism, interpretation, etc